Hepatic encephalopathy - Bustíos Sánchez, Carla (2007)
Hepatic encephalopathy is a neuro-psychiatric syndrome observed with great frequency in patients with advanced cirrhosis. The oldest and most popular theory about the genesis of this syndrome is the hypothesis of the ammonia generated in the large bowel, according to which this compound is not cleared by the hepatic reticulo endothelial system due to the presence of intrahepatic shunts, passing directly to the brain, easily crossing the blood brain barrier. It has recently been discovered that ammonia has a close relationship to the modulation of gamma aminobutiric acid (GABA), a potent neuroinhibitory peptide and at the same time with astrocytic activity. The diagnosis is mainly clinical, and computerized axial tomography, electroencephalography and other methods are only a complementary. In this article the mechanisms of hepatic encephalopathy, differential diagnosis and the limited therapeutic options currently available are reviewed.